Generation of program trajectories for robotic manipulators of point contact welding in the workspace with obstacles - M. M. Kozhevnikov; O. A. Chumakov; I. E. Ilushin; A. V. Hospad (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
New effective algorithms for generating paths of robotic manipulators for point-contact welding were proposed. They are based on the statistical model of the configuration space. Proposed algorithms, in contrast to the known ones, allow to take into account effectively geometric characteristics of the robotic complexes, kinematic and spatial limits, as well as the limits of the welding technology. The effectiveness of the developed algorithms confirmed by the results of testing in the experimental simulation tools.